2009
DOI: 10.1021/ja901045m
|View full text |Cite
|
Sign up to set email alerts
|

[{(η5-C5Me5)2Sm}4P8]: A Molecular Polyphosphide of the Rare-Earth Elements

Abstract: [{(eta(5)-C(5)Me(5))(2)Sm}(4)P(8)], a molecular polyphosphide of the rare-earth elements having a realgar core structure, was synthesized by a one-electron redox reaction of divalent samarocen and white phosphorus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
0
4

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 43 publications
2
81
0
4
Order By: Relevance
“…The average Pinner-Pcorner distance of 2.20 Å is close to the P-P interatomic distance in P4 (2.21 Å) (Corbridge and Lowe, 1952) or a recent updated gas phase value 2.1994(3) Å (Cossairt et al, 2010a). The structure of the P8 unit resembled that of (Cp*2Sm)4P8 (Konchenko et al, 2009). The P8 unit had been previously observed in some late transition metal complexes, which were obtained from the photolysis reaction of P4…”
supporting
confidence: 59%
See 2 more Smart Citations
“…The average Pinner-Pcorner distance of 2.20 Å is close to the P-P interatomic distance in P4 (2.21 Å) (Corbridge and Lowe, 1952) or a recent updated gas phase value 2.1994(3) Å (Cossairt et al, 2010a). The structure of the P8 unit resembled that of (Cp*2Sm)4P8 (Konchenko et al, 2009). The P8 unit had been previously observed in some late transition metal complexes, which were obtained from the photolysis reaction of P4…”
supporting
confidence: 59%
“…Among early transition metals, rare earths are more Lewis acidic, leading to a more pronounced mismatch in binding between their ions and phosphorous anions (Cui et al, 2008;Lv et al, 2011;Masuda et al, 2008). All known examples of lanthanide (Chart 22) (Konchenko et al, 2009;Li et al, 2011) and actinide (Scherer et al, 1991;Stephens, 2004) mediated P4 activation had involved low-valent metal complexes prior to our reports. For example, (Cp*2Sm)4P8 was obtained by vapor transfer of P4 to a toluene solution of Cp*2Sm over the course of a week in a low yield (ca.…”
Section: P 4 Activation By Scandium Arene Complexesmentioning
confidence: 74%
See 1 more Smart Citation
“…[5,6] On the contrary, early transition metal mediated P4 activation is much less investigated and rare-earth examples are rare. [7][8][9][10][11][12][13] Roesky et al reported the formation of (Cp * 2Sm)4P8 from slow vapour transfer of P4 into a toluene solution of Cp * 2Sm. [12] Our group recently reported a direct P4 activation by well defined scandium and yttrium naphthalene or anthracene complexes under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[16] The structure of the complex is very rare and can be described as a realgartype P 8 4À ligand trapped in a cage of four samarocenes. As no triple-decker sandwich complex of the rare-earth elements with a polyphosphide middle-deck bridging the metal centers is known, we focused our interest on the cyclo-P 5 ligand.…”
mentioning
confidence: 99%